Crosstalk between neutrophil extracellular traps and gut microbiota in ulcerative colitis: traditional Chinese medicine strategies - Feng, Yiyi; Liu, Yuchen; Qiu, Xiuxiu; Jiang, Jianfang; Mo, Jianling; Xv, Yichuan (Frontiers in Cellular and Infection Microbiology, 2025)
Ulcerative colitis (UC), a chronic and complex inflammatory bowel disorder, presents ongoing therapeutic challenges. Although multi-tiered anti-inflammatory strategies represent significant advances, issues like treatment resistance and adverse effects persist. Consequently, identifying more effective therapeutic targets and potentially curative strategies remains imperative. Emerging evidence underscores neutrophils, particularly through neutrophil extracellular trap (NET) formation, as pivotal contributors to UC pathogenesis. In affected individuals, excessive NET accumulation exacerbates intestinal inflammation, compromises the epithelial barrier, activates coagulation pathways, promotes resistance to biologic therapies, and may even facilitate malignant transformation. Critically, a bidirectional interplay exists between NETs and the gut microbiota (GM) in this disease. Recent research indicates that certain traditional Chinese medicine (TCM) herbal extracts and formulas hold promise for modulating aberrant NET generation and GM composition. This review examines the roles of NETs and GM in UC pathogenesis and synthesizes evidence on potential TCM-based interventions targeting these pathways, offering novel perspectives for future therapeutic development.